AB1080-HPR The Organizational and Environmental Factors That Affect Patient Satisfaction in Day Care Units. (15th July 2016) - Pavic Nikolic, M.; Huzjan, B.; Kosir Jost, S.; Perdan Pirkmajer, K.
Abstract : Background: Patients with inflammatory rheumatic disease, who are treated with biologics, often need a lifelong therapy and frequent examinations. Some of them receive biologics intravenously (i.v.) in a day care unit.Their satisfaction is an important indicator of quality in health care and is influenced by many yet undetermined nonclinical factors. Objectives: The aim of our study was to determine the circumstances that have important influence on satisfaction of patients in our day care unit. Methods: Patients treated in the day care unit of the Department of Rheumatology, University Medical Centre Ljubljana, Slovenia were enrolled from November 2014 to the end of January 2015. 130 questionnaires focusing on environmental adequacy of day care units, privacy during the treatments, organization of day care units, satisfaction with health care and access to phone advice were distributed. Data were analyzed using independent samples t-test when appropriate. Results: One hundred and nineteen patients treated in our day care unit were included. Their average age was 57 ± 12, 6 years old, 73, 9% of them were women. The most frequently represented rheumatic disease was rheumatoid arthritis (77, 3%), the average disease duration was 14, 7 years. Most patients (41%) were being treated with biological therapy for 3–5 years. Most patients in our day care unit organised their own transport to the hospital (73, 9%), 49, 6% of patients commuted from places which are more than 25 km away. According to our questionnaire suitability of treatment rooms, have only marginal, t statistically unimportant, impact on patient satisfaction (p=0, 050). The organization of work in daily hospital, the way of providing information about health condition, future treatment options, privacy during the treatment and possibility of obtaining information by phone all had important influence ob patient satisfaction (all p<0.005). Overcrowded rooms, high environmental temperatures in the summer, long waiting times for the treatment and the absence of the rheumatologist during the treatment in day-care unit all negatively affected patient satisfaction. Conclusions: Our study shows important connections between the level of patient satisfaction and environmental as well as organizational aspects of day care unit treatment. This data provide new opportunities for our day care unit environmental improvements and organizational changes. Disclosure of Interest: None declared